Handover Latencies in BCMP Networks - Gergely Biczok; Kristof Fodor; Balazs Kovacs (Communications - Scientific letters of the University of Zilina, 2004)
In this article, we give a short overview on wireless access networks and the BRAIN Candidate Mobility Protocol (BCMP). The two different handover mechanisms of BCMP are introduced. With the help of standard network tools and an own measurement program, latencies caused by both kinds of handovers were examined. We show that latency values are largely hardware-dependent and that by an adequate hardware configuration, BCMP provides smooth and fast handovers. This makes BCMP suitable for using with real-time applications, such as packetswitched voice or video.